Islamic Judicial Activism in Determining Child Maintenance: Ex Officio Authority and Peaceful Settlement in Indonesian Religious Courts - alamsyah, Alamsyah; Sukirman, Asrianti; Mukhlas, Oyo Sunaryo; Rosadi, Aden (Institut Agama Islam Negeri Curup, 2025)
This article examines the construction of Islamic law in determining child support after divorce through two mechanisms in Indonesia’s Religious Courts: amicable settlement (ṣulḥ) and judges’ ex officio authority. Although both have a clear legal basis, their practice continues to face challenges: amicable settlements are often compromise-based without objective evaluation of children’s needs, while ex officio rulings tend to be more responsive but lack uniformity due to the absence of standardized guidelines. Employing a juridical-empirical approach with content analysis of four representative decisions from the Bintuhan and Manna Religious Courts (2023–2024), this study identifies the legal considerations applied, assesses the adequacy of child support amounts, and compares the effectiveness of both mechanisms. The findings reveal that amicable settlements frequently result in insufficient child support, whereas ex officio rulings better protect children’s interests yet remain inconsistent. By integrating the principle of maqāṣid al-syarī‘ah, particularly ḥifẓ al-nasl (protection of lineage), this research introduces the concept of Islamic judicial activism, which positions judges as proactive actors in ensuring the child’s best interests. Theoretically, the study enriches global Islamic legal discourse by proposing a maqāṣid-oriented adjudication model that bridges normative texts, socio-economic realities, and substantive justice. Practically, it recommends that the Supreme Court establish national guidelines for child support determination based on cost-of-living standards, enhance judges’ capacity, and strengthen monitoring mechanisms for enforcement. Thus, this study not only contributes to comparative family law scholarship but also offers an innovative normative model for child protection in Muslim jurisdictions.